ANALYZING THE PERFORMANCE OF THE NATIONAL TEAM MEMBERS IN THE SPORT OF ORIENTEERING - Veronica MINOIU; George Emilian MINOIU (Universitaria Publishing House, Craiova, 2017)
Objective: Competitors in the sport of Orienteering must be able to race through different types of terrain in the shortest time possible. This paper aims to analyze the performance indices in all types of Orienteering events for some of the best members of the National Orienteering Team during 2017. Methods: The analysis was done based on statistical data collected from 24 National Team members using the WinSplits software. Results: The distribution of the performance indices differ throughout a competition and especially between different competitions and it is tightly correlated with the competitive experience in similar terrains. A higher training volume in similar terrain leads to better performance during the competition. Competitors with very good results during trial events but with reduced exposure to training in similar terrain have recorded diminished consistency but significant improvement throughout a race or during multi day events on the same type of terrain. Conclusions: Orienteers' performance can be improved by monitoring the indices that show which types of terrain are challenging and which are more suitable for them.